Integrated Language Strategies for Teaching Sets to Grade 7 Learners in a Philippine Public School: A One-Group Pretest-Posttest Study - Ashley Coleen S Ortiz; Douglas A Salazar (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study examined whether language strategies improve Grade 7 learners’ conceptual understanding of sets. It also explored how the learners perceived the use of these strategies in learning mathematics. Methodology: A one-group pre-test–post-test design was conducted with 27 low-performing Grade 7 learners from a public school in North Cotabato. The intervention usedocabulary building, composing with keywords, metacognitive prompts, defining formats for mathematical clarity, and a profile-and-frame approach in lessons on sets, subsets, union, and intersection. Quantitative data came from a researcher-made 40-item test, while qualitative data on learner perceptions were gathered through guided interviews. Main Findings: Learners’ mean scores increased from 12.93 (pre-test) to 20.04 (post-test), and the Wilcoxon Signed Rank Test indicated a statistically significant improvement in conceptual understanding (p = .001). Thematic analysis showed that language strategies supported clarity, retention, and engagement, though some learners experienced cognitive overload and language-related difficulties. Novelty/Originality of this study: This study demonstrates how the use of specific language strategies in teaching sets can enhance conceptual understanding of low-performing group of Grade 7 students. It also highlights the need to manage cognitive load and language demands, underscoring the importance of differentiated support when using language-rich approaches in mathematics instruction.